The measure of a man : a spiritual autobiography - Poitier, Sidney (San Francisco, CA : HarperSanFrancisco, 2007)
The acclaimed actor reveals the passion, spirituality, and intellectual fervor that have driven his life and career, citing the elements of his childhood that gave him his sense of worth and ethics
Includes index.
Keywords: Poitier, Sidney; Actors -- United States -- Biography